202k views
3 votes
How would this circle proof be set up?

How would this circle proof be set up?-example-1
User Anchandra
by
4.1k points

1 Answer

7 votes

Answer:

Explanation:

Given: Circle O with BT as a tangent at point B.

T is the midpoint of arc CD.

To prove: (CA)(TB) = (TA)(CT)

Since point T is the midpoint of arc CD,

Therefore, m(arc CT) = m(arc TD)

and m∠CAT ≅ m∠DAT

m(∠ACT) = 90° [Angle subtended by the diameter]

By applying tangent rule in triangles ACT and ABT,

tan(∠CAT) =
(CT)/(CA)

Similarly, tan(∠BAT) =
(TB)/(TA)

Since tan(∠CAT) = tan(∠BAT)

Therefore,
(CT)/(CA)=(TB)/(TA)

(CA) × (TB) = (CT) × (TA)

Hence proved.

User Zooblin
by
5.2k points